Home-based multidisciplinary interventions on skin adverse reactions in EGFR-TKI-treated patients with lung cancer: a protocol for a randomised controlled trial. Issue 11 (28th November 2022) - Du, Ruofei; Yang, Huashan; Zhou, Huiyue; Ma, Lixia; Getu, Mikiyas Amare; Chen, Changying; Wang, Tao
Abstract : Introduction: Here, we provide a feasible, well-designed protocol of a randomised controlled trial for the assessment of the effects of a home-based multidisciplinary intervention on the severity of skin adverse drug reactions and health-related indicators in patients with non-small cell lung cancer (NSCLC) under epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) therapy. Methods and analysis: The study will be a two-group, parallel randomised controlled trial conducted at patients' homes by a multidisciplinary team in Zhengzhou in Henan Province, China. Patients with NSCLC who received EGFR-TKI therapy and experienced adverse skin reactions will be randomised and receive either ordinary care or home-based multidisciplinary interventions. The intervention will be divided into an intensive stage (6 weeks) and a maintenance stage (6 weeks) with baseline and follow-up assessment. Interventions in the intensive stage will include general interventions such as health education, follow-up, behaviour guide and social support and targeted interventions such as skill training, coping with adverse drug reaction and problem-solving. The measures that will be carried out in maintenance stage are continuous interventions consisted of an intensive intervention. The multidisciplinary team will be responsible for managing skin adverse drug reactions as required at patients' homes. Data collection and analysis will be performed by researchers at baseline, the end of the sixth week of intervention and the third month after the intervention. The primary outcome is the degree of skin adverse drug reactions, while the secondary outcomes, for example, self-management ability, quality of life, outpatient visits and health economics indicators, will also be presented. Ethics and dissemination: This study was reviewed and approved by the Ethics Committee of Zhengzhou University (No. ZZUIRB-2020-97). Findings will be available to patients, clinicians, nurses, pharmacists, community medical staff, funders and health policymakers through peer-reviewed publications, social media and patient support groups. Trial registration number: Chinese Clinical Trials Registry (ChiCTR2000040643).